Nanoemulsions versus lyotropic liquid crystals (Asian Journal of Pharmaceutics (AJP), 2014)
Nanoemulsions have gained great accolade in pharmaceutical and food industries, because of integer features, such as optical clarity, ease of preparation, thermodynamic stability, and increased surface area. They are isotropic, nonequilibrium, kinetically stable system of oil, defined blend of surfactant and co-surfactant and water, which serve as vehicles for the delivery of active pharmaceutical ingredients as well as other bio-actives. Both high and low-energy methods have already been exploited to design this system. This review clarify the recurrent confusions found in the literature regarding the difference between nanoemulsions and lyotropic liquid crystals, components, method of preparation, evaluation parameters, and stability issues, which have been described and also the significance of pseudo-ternary phase diagram has been addressed.